Tolkāppiyam, Eḻuttatikāram, Puḷḷi mayaṅkiyal : uraivaḷam - Sivalingam, A. (Publication / International Institute of Tamil Studies ;, 1983)
Compilation of commentaries on Puḷḷimayaṅkiyal, part of Tolkāppiyam, ancient Tamil grammar by Tolkāppiyar.